Law of the sea : from Grotius to the International Tribunal for the Law of the Sea : liber amicorum Judge Hugo Caminos - Castillo, Lilian del; Caminos, Hugo (Brill Nijhoff, 2015)
Law of the Sea, From Grotius to the International Tribunal for the Law of the Sea: Liber Amicorum Judge Hugo Caminos honors the accomplished career path of a distinguished scholar, professor, diplomat and judge in the global field of the Law of the Sea.